Performance evaluation and reference interval establishment of Abbott Alinity thyroid-stimulating hormone receptor antibody (TRAb) assay for diagnosing Graves’ disease - Hao Xue; Bowen Li; Xiaowei Wang; Junhan Zhao; Yaoming Yan; Jize Lao; Ling Ji; Yong Xia (PLoS ONE, 2026)
Objectives This study aims to evaluate the analytical and clinical performance of the Abbott Alinity TRAb chemiluminescent microparticle immunoassay and establish the reference interval for healthy Chinese populations. Methods The precision, analytical sensitivity and linearity of Abbott TRAb assay were verified in accordance with the Clinical and Laboratory Standards Institute guidelines. A total of 300 samples from patients with Grave’s disease (GD) and other thyroid diseases were collected for method comparison and clinical performance verification. The performance of Abbott and Snibe TRAb assays was compared to Roche TRAb assay by correlation and agreement analysis. The diagnostic performance of Abbott TRAb assay was analyzed via receiver operating characteristic (ROC) analysis. The reference interval of Abbott TRAb was established from a cohort of 366 healthy individuals. Results The Abbott Alinity TRAb assay demonstrated excellent precision, with repeatability (CV%) ranging from 1.04% to 5.92%, and within-laboratory imprecision (CV%) ranging from 1.09% to 5.92%. Manufacturer-claimed limits of blank, detection, and quantification were successfully verified. Linearity was confirmed from 1.14 to 47.72 IU/L. Strong correlation was observed between Abbott and Roche assays (Spearman r = 0.972; slope = 1.060), while Snibe and Roche assays showed lower correlation (r = 0.784). Concordance analysis showed the total agreement with Roche results were 97.7% for Abbott and 96.7% for Snibe. Diagnostic accuracy of the Abbott TRAb assay for GD was high, yielding an area under curve (AUC) of 0.999, sensitivity of 98.4%, and specificity of 99.4% at an optimal cutoff of 2.89 IU/L. The upper reference limits at 95 th percentile and 97.5 th percentile for healthy Chinese population using Abbott TRAb assay were 1.56 IU/L and 1.95 IU/L, respectively. Conclusions This study demonstrated the robustness of Abbott Alinity TRAb CMIA in clinical use with its verified analytical and clinical performance and established the reference interval for Chinese population.